Semiotika Kampanye Politik Melalui Papan Reklame - Muhammad Fadeli; Tira Fitria Wardhani; Andri Setiawan (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2022)
The year 2020 was "political battle" year for the City of Surabaya with the election of mayor and deputy mayor on December 9, 2020. The election of the mayor and deputy mayor of Surabaya 2020 is very interesting to study because of the election of two potential candidates from the coalition of major parties in Surabaya. Candidate number one Ery Cahyadi and Armuji was to challenge candidate number two Machfud Arifin and Mujiaman. Even though technology has advanced so much, billboard is still used today for political campaign media. Billboard is able to attract the attention of the general public, especilaay for the road users. This study aims to find out the meaning of message conveyed in the billboards as the medium for political campaign from the candidates of mayor and deputy mayor of Surabaya 2020. This research is based on Roland Barthes' semiotic theory using qualitative descriptive research. Data was collected during November 2020 through the documentation of billboards on the Surabaya City main roads and made observations on two billboards based on Roland Barthes' semiotic theory. The semiotics that emerged in the campaigns of the two candidates have found a relationship between the signifier and the signified that clearly explains the denomination order, then there is also an interaction between the sign and the reader's emotional feelings, as well as cultural values that lead to a connotative order so that a separate meaning is found in the text in each ad version. The protrusion of signs and pictures shows the performance, existence, competence, relations, and concern of the candidates for mayor and deputy mayor of Surabaya.